2007
DOI: 10.1056/nejmoa060651
|View full text |Cite
|
Sign up to set email alerts
|

Mutations inVANGL1Associated with Neural-Tube Defects

Abstract: Neural-tube defects such as anencephaly and spina bifida constitute a group of common congenital malformations caused by complex genetic and environmental factors. We have identified three mutations in the VANGL1 gene in patients with familial types (V239I and R274Q) and a sporadic type (M328T) of the disease, including a spontaneous mutation (V239I) appearing in a familial setting. In a protein-protein interaction assay V239I abolished interaction of VANGL1 protein with its binding partners, disheveled-1, -2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
283
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(302 citation statements)
references
References 17 publications
16
283
2
1
Order By: Relevance
“…Thus this mouse model system may provide a means to locate and test human NTD candidate gene(s). Very few genes have been linked to human NTD susceptibility to date, including MTHFR (40) and VANGL1 (25), and mapping additional human susceptibility factors would be a significant step toward understanding human NTDs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus this mouse model system may provide a means to locate and test human NTD candidate gene(s). Very few genes have been linked to human NTD susceptibility to date, including MTHFR (40) and VANGL1 (25), and mapping additional human susceptibility factors would be a significant step toward understanding human NTDs.…”
Section: Discussionmentioning
confidence: 99%
“…Neural tube defects in KO mice [96] Neural tube defects in VANGL1/2 DKO mice [78] VANGL2 Neural tube defects in KO mice [97] Neural tube defects in VANGL1/2 DKO mice [78] Causes precocious differentiation of neural progenitors into early-born neurons [79] Regulates asymmetric division in mouse SVZ [72] ROR1/2 Implicated in neurite extension [98] Implicated in synapse formation [99] Regulates differentiation in primary mouse neural progenitors…”
Section: Vangl1mentioning
confidence: 99%
“…Indeed, missense mutations in VANGL2 and its homolog VANGL1 have been identified in patients with spinal bifida (Kibar et al 2007(Kibar et al , 2009(Kibar et al , 2011 and miscarried fetuses with cranial NT defects such as anencephaly (Lei et al 2010). These studies showed conclusively that disruption of PCP signaling is an important causative factor of NTDs in humans.…”
Section: Neural Tube (Nt) Closurementioning
confidence: 94%